2012
DOI: 10.1007/s11606-012-2155-9
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity: Obscuring the Diagnosis of Aortic Stenosis in a Patient with Cardiogenic Wheezing

Abstract: We report the case of a morbidly obese 65-year-old female who presented with repeated hypotensive episodes following dialysis. She was misdiagnosed as suffering from asthma, and eventually was found to have severe aortic stenosis. Obesity has become a common and formidable obstacle to gathering important diagnostic information in patients. Modern diagnostic lab tests and imaging modalities such as transthoracic echocardiography (TTE) can provide spurious data in the morbidly obese population, which can ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Several studies outside the field of orthopaedics have demonstrated that obesity can affect the reliability of the physical examination. 3 , 4 , 6 , 11 , 22 , 33 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies outside the field of orthopaedics have demonstrated that obesity can affect the reliability of the physical examination. 3 , 4 , 6 , 11 , 22 , 33 …”
mentioning
confidence: 99%
“…Several studies outside the field of orthopaedics have demonstrated that obesity can affect the reliability of the physical examination. 3,4,6,11,22,33 Orthopaedic literature on the effect obesity has on physical examination is scarce. Anthropometric measurements of midarm circumference, subscapular, and triceps skinfold thicknesses are on the rise in concurrence with the increase in mean BMI and obesity rates.…”
mentioning
confidence: 99%